Power graphs: A survey - Jemal Abawajy; Andrei Kelarev; Morshed Chowdhury (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2013)
This article gives a survey of all results on the power graphs of groups and semigroups obtained in the literature. Various conjectures due to other authors, questions and open problems are also included.